A review of vaccine effects on women in light of the COVID-19 pandemic (2020)
The pandemic situation triggered by the spread of COVID-19 has caused great harm worldwide. More than six million people have been infected, and more than 360,000 of them have died. This is the worst catastrophe suffered by mankind in recent history. In the face of this severe disaster, people all over the world are frightened of the prospect of facing an outbreak or an annual recurrence. However, the development of a vaccine will help control the impact of COVID-19. Women in particular have been more seriously affected by the pandemic. Since the pressure and physical load they suffer are often greater than what men endure, women are more threatened by COVID-19. Though women have a poorer quality of life and work and face worse economic conditions, they also tend to have better physiological immunity than men, which can ease the effect of COVID-19. The early development of a vaccine against COVID-19 is an important issue that must take into consideration women’s better immune response to the virus along with the technique of hormone regulation. Relevant research has been conducted on female-specific vaccines in the past, and women’s issues were considered during those clinical trials to ensure that complications and antibody responses were positive and effective in women. National policies should also propose good strategies for women to be vaccinated. This could improve consciousness, give women a better vaccination experience, enhance their willingness to vaccinate, and protect them from COVID-19 infection.